1997
DOI: 10.1093/nar/25.3.597
|View full text |Cite
|
Sign up to set email alerts
|

Replication bypass and mutagenic effect of alpha-deoxyadenosine site- specifically incorporated into single-stranded vectors

Abstract: alpha-2'-Deoxyadenosine (alpha) is a major adenine lesion produced by gamma-ray irradiation of DNA under anoxic conditions. In this study, single-stranded recombinant M13 vectors containing alpha were constructed and transfected into Escherichia coli to assess lethal and mutagenic effects of this lesion. The data for alpha were further compared with those obtained with M13 vectors containing normal A or a model abasic site (F) at the same site. The transfection assay revealed that alpha constituted a moderate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 43 publications
3
32
1
Order By: Relevance
“…We had reported previously a similar observation where Dpo4 incorporated nucleotides onto a blunt-end DNA substrate with the following preference: dATP Ͼ dTTP Ͼ dCTP Ͼ dGTP (28). In addition, a previous report demonstrated a nearly equal probability of incorporation of dATP and dTTP opposite this lesion in vivo (33). Ultimately, we do not know the reason for the increased probability of dTTP incorporation into AP-8, but we suspect this trend is likely polymerase-dependent.…”
Section: ϫ5mentioning
confidence: 69%
“…We had reported previously a similar observation where Dpo4 incorporated nucleotides onto a blunt-end DNA substrate with the following preference: dATP Ͼ dTTP Ͼ dCTP Ͼ dGTP (28). In addition, a previous report demonstrated a nearly equal probability of incorporation of dATP and dTTP opposite this lesion in vivo (33). Ultimately, we do not know the reason for the increased probability of dTTP incorporation into AP-8, but we suspect this trend is likely polymerase-dependent.…”
Section: ϫ5mentioning
confidence: 69%
“…112 a-Deoxyadenosine is a moderate block to DNA synthesis in vitro 113 and in E. coli, one-base deletions are found. 114 Spiroiminodihydantoin (Sp) and guanidinohydantoin (Gh), the further oxidation products of 8-oxoG, are both strong blocks to Klenow fragment and Klenow fragment exo À with A and G being primarily inserted opposite the lesions. 115,116 A crystal structure of Gh with a replicative polymerase shows Gh to be extrahelical and rotated towards the major groove and no longer in a position to serve as a template for an incoming base.…”
Section: Consequences Of Unrepaired Oxidative Dna Damagesmentioning
confidence: 99%
“…More interestingly, the nucleotide forms of FapyG and FapyA epimerize in solution, giving rise to a mixture of ␤-and ␣-anomers with respect to the orientation of the N-glycosidic bond around sugar C-1Ј. We have previously shown that the ␣-anomer of 2Ј-deoxyadenosine (␣dA) site-specifically introduced into oligonucleotide templates or M13 vectors constitutes moderate to fairly strong replication blocks in vitro and in vivo (57,58), exhibiting an effect similar to that of mFapyG. However, there are several differences between ␣dA and mFapyG concerning the responses to DNA polymerase and repair enzyme.…”
Section: Figmentioning
confidence: 99%